Hospitalization for respiratory syncytial virus in the paediatric population in Spain. - Vicente, D. (Cambridge University Press, 2003)
The aim of this population-based retrospective study was to determine the incidence of hospitalization for community-acquired, laboratory-confirmed respiratory syncytial virus (RSV) infection in an unselected paediatric population from southern Europe. The study was performed in an area with 15,700 children aged less than 5 years attended by a single hospital. The presence of RSV in nasopharyngeal aspirates from children with acute respiratory infection treated in the hospital was investigated in four seasons (July 1996-June 2000). A total of 390 episodes of hospitalization for RSV infection were detected and 83.3% of the children were aged less than 1 year old. The annual hospitalization rate was 37/1000 for infants aged less than 6 months and 25/1000 for those aged less than 1 year. During the study period, 2.5% of the infants younger than 1 year and approximately 5% of those younger than 3 months were hospitalized for RSV infection. The mean length of hospital stay was 5.9 days. Seven per cent of the patients required admission to the intensive care unit and more than half of these children were aged less than 1 month. In Spain, community-acquired RSV infection is a highly frequent cause of hospitalization in young children, especially in those aged less than 1 year. Prevention of RSV infection, through the development of vaccines and/or other strategies, should be a public health priority.